Foreign Policy Attitudes of Political Parties in Serbia: How Far From the East, How Close to the West? - Abdula, Sevba; Erken, Ali (Balkan Politics: Political Parties in the Balkans, 1991-2024, 2025)
Following democratic changes in 2000, the new Serbian (Yugoslavian) govern-ment proclaimed European and Euro-Atlantic integration as “the basis of the country’s foreign policy orientation” (Dragojlović et al., 2011: 295). While acces-sion to the European Union (EU) was placed as the primary foreign policy goal in 2001, the 2004 Defence Strategy additionally labelled joining NATO as one of the country’s “vital security and defence interests” (Скупштина СЦГ, 2004). Howe-ver, such an orientation has been constantly challenged by the far-right Serbian Radical Party (SRS), which was winning almost 30% of the popular votes in th-ree consecutive parliamentary election cycles (2003, 2007, 2008). Together with a gradual shift of the national-conservative Democratic Party of Serbia (DSS) towards more Eurosceptic positions and its advocating for the country’s military and political neutrality (Коштуница, 2013), pro-European forces embodied in the Democratic Party (DS) were not sufficiently strong to accelerate internal re-forms and move Serbia closer to the EU.